Upregulation of lncRNA plasmacytoma variant translocation 1 predicts poor prognosis in patients with muscle-invasive bladder cancer. Issue 28 (10th July 2020) - Li, Bin; Guo, Li-hua; Ban, Zi-qin; Liu, Lu; Luo, Lei; Cui, Tong-yue
Abstract : Abstract: LncRNA plasmacytoma variant translocation 1 (PVT1) has been recognized as an oncogenic lncRNA, which participates in the migration and invasion of many kinds of cancer cells and the development of cancers. In the present study, we explored its clinical significance and prognostic value in muscle invasive bladder cancer (MIBC). A total of 98 MIBC patients' samples were collected, who had undergone radical cystectomy from the March 2013 to December 2018. The associations between PVT1 expression and clinical data were calculated using the Chi 2 -test. Overall survival curves were determined by the Kaplan–Meier technique and contrasted via log-rank test. We utilized univariate and multivariate Cox proportional hazard models to examine the HR and 95% CI. The expression levels of PVT1 were significantly higher in MIBC tissues than that in normal bladder tissues ( P  < .001). PVT1 expression was significantly correlated with tumor grade ( P  = .009), margin ( P  = .002), T stage ( P  = .02), and lymph node metastasis ( P  < .001). MIBC patients with high PVT1 expression level had shorter overall survival than those with low PVT1 expression level (log-rank test, P  = .004). Multivariate Cox regression analysis showed that PVT1 expression level (HR = 2.381, 95% CI: 1.821–7.012, P  = .014) was an independent factor in predicting the overall survival of MIBC patients. In summary, increased PVT1 expression in MIBC patients is correlated with a higher MIBC stage and is significantly associated with poor prognosis for MIBC patients, which may provide new insights into new therapeutic strategy and postoperative intervention against bladder cancer.